‘De zoon, op wie zij trots was’. Voorgeschiedenis van de breuk tussen het Nederlandsch Tijdschrift voor Geneeskunde en de Nederlandsche Maatschappij tot Bevordering der Geneeskunst, 1856-1945 - Schoolmann, Bastiaan; Flipse, Ab (Studium, 2019)
‘The son she was proud of’: History of the separation between the Dutch Journal of Medicine and the Dutch Organization for the Advancement of Medicine, 1856-1945This article analyses the relationship between the Nederlandsch Tijdschrift voor Geneeskunde (NTvG) (the Dutch Journal of Medicine) and the Nederlandsche Maatschappij tot Bevordering der Geneeskunst (the Dutch Organization for the Advancement of Medicine) in the period 1856-1945. The establishment of the weekly journal in 1856 promised a fruitful alternative for the staggering monthly periodical of the Organization, in which it published its transactions earlier. Although the relationship between the Organization and the Journal, which was called the ‘official organ’, was sometimes characterized as one between a mother and a child, the cooperation soon became troubled by conflicting interests, ultimately stemming from the journal’s increasingly scientific focus. The Organization was dissolved during the Second World War, but when it was re-established afterwards it chose the newly established journal, Medisch Contact, as their official partner, a decision that apparently was based on the events during the War solely. In this article we argue, however, that there was a longer, troubled relationship, which almost caused earlier endings of their partnership.